Effect of additional heat treatment of a Pd-Au-Ag metal-ceramic alloy on hardness change during simulated porcelain firing - Kim, Sung-Min; Park, Soo-Chul; Seol, Hyo-Jung (International Journal of Engineering and Technology, 2019)
This research aims to investigate the effect of softening for dental Pd-Au-Ag metal-ceramic alloy when further treated with second heat treatment through simulated porcelain firing. Through experimental procedures, it was found that the hardness rating of the alloy was very much consistent throughout, and after the degasification process. Results showed that further heat treatments on the alloy did not enhance its hardness rating. Hence confirming that hardness is not largely affected in initial stages of porcelain firing process. However, in the later stages, throughout the heating process, the hardness did not decline, but rather had a positive effect. The alloy consists of matrix lattices and precipitates. The matrices were in the form of a Pd-Au-Ag-rich (Î±) â„« type face-centered cubic (FCC) structure with lattice parameter of a200= 3.989, and the precipitates were Pd3Sn (Î²) of AuCu3 type.Â
Keywords: Second Heat Treatment; Pd-Au-Ag Metal Ceramic Alloy; Simulated Porcelain Firing; Hardness change